Brigatinib can inhibit proliferation and induce apoptosis of human immortalized keratinocyte cells - Yang, Qi; Zhao, Dan; Ju, Linjie; Cao, Peng; Wei, Jifu; Liu, Zhixian (Frontiers in Pharmacology, 2025)
BackgroundBrigatinib is approved in multiple countries for the treatment of patients with anaplastic lymphoma kinase (ALK)-positive non-small cell lung cancer (NSCLC). Despite its superior efficacy, the dermal toxicities caused by brigatinib cannot be overlooked. However, its underlying mechanism remains unknown.MethodsThe effects of brigatinib on the proliferation ability of human immortalized keratinocyte (HaCaT) cells were evaluated using Cell Counting Kit-8 (CCK-8) proliferation, colony formation, and 5-ethynyl-2′-deoxyuridine (EdU) incorporation assays. The effects of brigatinib on apoptosis were detected using Annexin FITC/PI and Acridine Orange (AO) staining assays. Cell cycle was assessed with flow cytometry. An analysis of transcriptome by RNA sequencing procedures (RNA-seq) was performed to reveal the key regulatory genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to find out the biological function and related signal pathways. The expressions of amphiregulin, epiregulin and transforming growth factor alpha (TGFA) and the protein levels of Phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) and Cleaved-Caspase three were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot assay.ResultsBrigatinib inhibits cell proliferation with an IC50 value of 2.9 μmol/L and significantly increases apoptosis rates. Transcriptome sequencing (RNA-seq) indicates that brigatinib could significantly downregulate the expression of amphiregulin, epiregulin and TGFA. In addition, we demonstrated that brigatinib reduced the protein expression of amphiregulin, epiregulin, TGFA, PI3K, AKT and phosphorylated AKT (p-AKT).ConclusionThis study confirms the inhibition of HaCaT cells growth and progression by brigatinib and highlights the potential value of the PI3K/AKT pathway as a therapeutic target for brigatinib-induced dermal toxicities.